MODEL KUALITAS LAYANAN DAN PENERAPAN FUNGSI KUALITAS DALAM UPAYA PENINGKATAN NILAI PENJUALAN JASA BENGKEL MOBIL SHOP AND DRIVE RADIO DALAM - Suwanda (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2023)
Shop and Drive is one of the retail spare parts service companies facing challenge in achieving sales tergets. The problem arises from a lack of customer loyalty dua to dissatisfaction with the received service, not meeting their expectations. This situation necessities Shop and Drive Radio Dalam to enhance service quality by providing excellent customer service to achieve optimal renenue. Customer satisfaction is measured using the Serqual method. To prioritize areas for omprovement, improvtance performance analysis is employed. The results of improvtance performance analysis are utilized as the basis for improvement through the quality function deployment method. Based on the quality function deployment results, improvement actions are identified, including performance evaluation, regular training emphasizing SOP implementation, offering a more comprehensive spare parts inventory, and enhancing understanding of delivering excellent service. The improvements led to increased customer satisfaction across all attributes. The analysis comparing sales performance before and after the enhancements increase in sales achievements.